A high-wear-resistance mica composite for new energy vehicle batteries and a preparation method thereof
Patent Information
- Application Number
- CN202311500901.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-13
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-11-13
AI Technical Summary
但是,柔性云母复合材料依旧存在问题:柔性云母基材表面的耐磨性较差,在使用过程中柔性云母复合材料易出现掉粉问题,不仅会影响无尘车间的作用环境,不利于产品的品控,最终会影响锂离子电池组的寿命和使用安全
1、本申请具有优良防火阻燃安全性能、绝缘抗击穿性能的同时具有良好的耐磨损性能和一定的柔韧性,用于汽车电芯可提升整车的热失控防护安全性能。
Abstract
Description
Technical Field
[0001] This application relates to the field of flexible mica composite materials technology, and in particular to a high wear-resistant mica composite material for new energy vehicle batteries and its preparation method. Background Technology
[0002] Flexible mica composite materials possess excellent fire-retardant properties and electrical insulation safety, and are now widely used in the field of thermal runaway protection for new energy vehicles. The power battery pack of new energy vehicles, as the core component for energy storage and output, determines the lifespan and safety performance of the vehicle.
[0003] The electrode volume in a lithium-ion battery pack changes during charging and discharging, as well as with local temperature variations. These changes alter the volume of individual battery cells, leading to significant stress between them and impacting the battery pack's lifespan and safety. Flexible mica composite materials, placed between individual cells, can provide cushioning, shock absorption, and heat insulation, effectively improving the battery pack's lifespan and safety. However, flexible mica composite materials still present challenges: the surface of the flexible mica substrate has poor abrasion resistance, and the composite material is prone to powder shedding during use. This not only affects the cleanroom environment and hinders product quality control but also ultimately impacts the battery pack's lifespan and safety. Summary of the Invention
[0004] To address the aforementioned technical problems, this application provides a high wear-resistant mica composite material for new energy vehicle batteries and its preparation method.
[0005] Firstly, the high wear-resistant mica composite material for new energy vehicle batteries provided in this application is achieved through the following technical solution: A high-wear-resistant mica composite material for new energy vehicle batteries includes a flexible mica substrate, which is made of an organosilicon resin and a mica composition through a hot-pressing process. Grooves are integrally formed on the surface of the flexible mica substrate through hot pressing. These grooves are filled with nano-ceramic fillers. The nano-ceramic fillers include at least one of nano-α-phase alumina, nano-tetragonal zirconium oxide, nano-magnesium oxide, nano-yttrium oxide, nano-silicon dioxide, nano-aluminum nitride, nano-silicon nitride, nano-zirconium nitride, nano-zirconium boride, titanium nitride whiskers, and silicon nitride whiskers. The particle size of the nano-ceramic fillers is 20-800 nm. The nano-ceramic fillers located in the grooves on the surface of the flexible mica substrate are laser-sintered to form "ceramic-cured bonds," which connect adjacent mica compositions together, preventing frictional detachment.
[0006] This application possesses excellent fire-retardant safety performance, insulation and breakdown resistance performance, as well as good wear resistance and a certain degree of flexibility. When used in automotive battery cells, it can improve the thermal runaway protection safety performance of the entire vehicle.
[0007] Preferably, the thickness of the flexible mica substrate is controlled at 0.20-1.0 mm, and the adhesive content is controlled at 10-16 wt%; the mica composition is composed of mica powder treated with a surface modifier and toughening filler in a mass ratio of (90-98):(2-10); the mica powder in the mica composition is at least one of phlogopite powder, muscovite, biotite, and fluorophlogopite; the toughening filler is at least one of aramid short fiber, glass short fiber, γ-alumina fiber, and aluminum borate whiskers.
[0008] Preferably, the mica powder in the mica composition has a particle size of 30-60 μm; the aramid short fibers, glass short fibers, and γ-alumina fibers in the toughening filler have a length of 10-500 μm; the aluminum borate whiskers have a particle size of 0.3-10 μm; and the surface modifier in the mica composition is at least one of methacryloyloxysilane, vinyl silane, and titanate coupling agent.
[0009] Preferably, the thickness of the flexible mica substrate is controlled at 0.20-0.40 mm, and the adhesive content is controlled at 12-14 wt%; the mica powder in the mica composition is composed of phlogopite powder and fluorophlogopite in a mass ratio of (3-4):1; the mica composition is composed of mica powder treated with a surface modifier and toughening filler in a mass ratio of (94-96):(4-6); the toughening filler is composed of aramid staple fiber and aluminum borate whiskers in a mass ratio of (90-98):(2-10); the aramid staple fiber is Kevlar aramid staple fiber with a fineness of 2-3 DTEX and a length of 0.2-0.4 mm; the surface modifier is composed of methacryloyloxysilane KH570, vinylsilane KH-151, and titanate coupling agent KR 138S in a mass ratio of (1-4):(1-4):(0.5-2).
[0010] The flexible mica substrate in this application has good flame retardancy and fire resistance as well as insulation and breakdown safety performance. It also has good flexibility, which meets the requirements of manufacturing three-dimensional irregular parts with flexible mica substrate, and plays a better role in thermal runaway protection.
[0011] Preferably, the nano-ceramic filler is composed of 40-60 parts of nano-α-phase alumina with an average particle size of 10-200 nm, 5-20 parts of nano-tetragonal phase zirconia with an average particle size of 50-200 nm, 1-3 parts of nano-magnesium oxide with an average particle size of 50-200 nm, 1-3 parts of nano-silica with an average particle size of 20-50 nm, 1-3 parts of nano-aluminum nitride with an average particle size of 50-500 nm, 1-3 parts of nano-silicon nitride with an average particle size of 20-800 nm, 0.2-0.5 parts of titanium nitride whiskers, and 0.2-0.5 parts of silicon nitride whiskers; the length of the titanium nitride whiskers and silicon nitride whiskers is 5-20 μm, and the aspect ratio is 20-40.
[0012] By optimizing the nano-ceramic filler and its particle size, the prepared flexible mica composite material can be guaranteed to have wear resistance and a certain degree of flexibility, which can meet the requirements of manufacturing three-dimensional irregular parts and expand its application range.
[0013] Preferably, the organosilicon resin is made of 100 parts of methylphenyl silicone resin, 25-60 parts of organic solvent, 0.3-0.6 parts of diethylenetriamine, 40-60 parts of polysiloxane crosslinking agent, and 1-3 parts of nano-sized vitrified ceramic powder; the polysiloxane crosslinking agent is at least one of JNC's FM-3321 type diamine-terminated reactive silicone, FM-3325 type diamine-terminated reactive silicone, FM-7721 type diacetyl reactive silicone, and FM-7725 type diacetyl reactive silicone.
[0014] Preferably, the polysiloxane crosslinking agent is composed of JNC's FM-3325 diamine-terminated reactive silicone and FM-7721 diacetyl reactive silicone in a molar ratio of (3-4):1.
[0015] Preferably, the preparation method of the organosilicon resin is as follows: A precisely measured amount of polysiloxane crosslinking agent, methylphenyl silicone resin, and 40-60% (by mass) of diethylenetriamine are added to a reaction vessel. The mixture is heated to 60-65°C at a magnetic stirring speed of 60-120 rpm and held for 100-160 seconds. After cooling to 0-4°C via an ice-salt bath, an organic solvent is added, and the mixture is stirred at 80-160 rpm for 5-10 minutes. Then, the remaining diethylenetriamine is added, and the mixture is stirred at 40-60 rpm for 100-160 seconds to obtain the organosilicon resin. The storage temperature of the obtained organosilicon resin should preferably be controlled at 0-4°C.
[0016] This application optimizes the design of the silicone resin to not only meet the requirements of its bonding stability and flame retardancy, but also to meet the requirement that the prepared flexible mica substrate can be used for the manufacture of three-dimensional irregular parts, thus expanding its application scope.
[0017] Secondly, the preparation method of a high wear-resistant mica composite material for new energy vehicle batteries provided in this application is achieved through the following technical solution: A method for preparing a high-wear-resistant mica composite material for new energy vehicle batteries includes the following steps: Step 1: Prepare the silicone resin and simultaneously treat the mica composition with a surface treatment agent. Step 2: The prepared silicone resin and the mica composition treated with the surface treatment agent are mixed evenly to obtain a molded mica slurry. The molded mica slurry is transferred to a hot press mold and heated to remove the organic solvent components in the molded mica slurry. Then, a stainless steel mold plate is used to perform leveling and molding treatment to obtain a preform. The molding surface of the stainless steel mold plate is formed with a grid groove, and the surface of the preform is formed with a grid-shaped groove area. Step 3: Mix the prepared nano-ceramic filler with high-purity nitrogen gas at a ratio of (0.1-2):(98-99.9) to form a deposition gas. The resulting deposition gas has a flow rate of 0.3-0.5 m / s. The sedimentation area formed between the delivery pipe of the deposition gas and the preform moves along the length of the preform at a speed of 4-8 cm / s, thus performing a full-coverage sedimentation treatment on the surface of the preform. Step four: First hot pressing treatment, with a platen temperature of 80±0.5℃, a pressure of 0.20-0.25Mpa, and a continuous hot pressing time of 60±2s; Second hot pressing treatment, with a platen temperature of 130±0.5℃, a pressure of 0.50-0.60Mpa, and a continuous hot pressing time of 120±2s; Third hot pressing treatment, with a platen temperature of 180±0.5℃, a pressure of 0.80-1.0Mpa, and a continuous hot pressing time of 150±5s; Fourth hot pressing treatment, with a platen temperature of 120±0.5℃, a pressure of 0.50-0.60Mpa, and a continuous hot pressing time of 60±5s. After cooling to 80-85℃, laser sintering is performed to obtain a high wear-resistant flexible mica composite material.
[0018] The preparation method provided in this application is relatively simple, with low production difficulty, and the process is easy to standardize and scale up. It can ensure the quality stability of products in the same batch while achieving industrialized production and optimizing and reducing production costs.
[0019] Preferably, the laser sintering processing parameters are: laser diameter 0.02-0.08mm, laser power 120-240W, scanning rate 0.2-0.4mm / s, and the laser scanning path moves along the length direction of the obtained preform to perform 1-2 full-coverage laser sintering processes, and then cools to room temperature to obtain a high wear-resistant flexible mica composite material.
[0020] By adopting the above technical solutions, the wear resistance of flexible mica composite materials can be improved, while also ensuring the quality stability of products in the same batch, which facilitates better market recognition and is beneficial to subsequent development and sales.
[0021] In summary, this application has the following advantages: 1. This application has excellent fire-retardant safety performance, insulation and breakdown resistance performance, good wear resistance and a certain degree of flexibility. When used in automotive battery cells, it can improve the thermal runaway protection safety performance of the whole vehicle.
[0022] 2. This application optimizes the design of the silicone resin, which not only meets the requirements of its bonding stability and flame retardancy, but also meets the requirement that the prepared flexible mica substrate can be used to manufacture three-dimensional irregular parts, thus expanding its application scope.
[0023] 3. The preparation method provided in this application is relatively simple, the production operation is easy, and the process is easy to standardize and scale up. It can ensure the quality stability of the same batch of products while achieving industrialized production and optimizing and reducing production costs. Detailed Implementation
[0024] To further understand the present invention, preferred embodiments are described below with reference to examples. However, it should be understood that these descriptions are merely for illustrating the features and advantages of the present invention and are not intended to limit the scope of the claims. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired results.
[0025] It is particularly important to note that all similar substitutions and modifications will be obvious to those skilled in the art and are considered to be included within the scope of this invention. The methods and applications of this invention have been described through preferred embodiments, and those skilled in the art will readily be able to modify or appropriately alter and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to implement and apply the technology of this invention. While it is believed that those skilled in the art will fully understand the following terms, the following definitions are set forth to help illustrate the subject matter disclosed in this invention.
[0026] As used herein, the term "comprising" is synonymous with "including," "containing," or "characterized in," and is inclusive of endpoints or open-ended, and does not exclude additional unstated elements or method steps. "Comprising" is a technical term used in the language of claims, meaning that the stated element is present, but other elements may be added and still form a construction or method within the scope of the claims. Example
[0027] A high-wear-resistant mica composite material for new energy vehicle batteries includes a flexible mica substrate and a foamed material laminated to the surface of the flexible mica substrate. The surface of the flexible mica substrate without the foamed material is integrally hot-pressed to form grooved regions, which are filled with nano-ceramic fillers. The nano-ceramic fillers within the grooved regions on the surface of the flexible mica substrate are laser-sintered to form "ceramic-cured bonds." These "ceramic-cured bonds" connect adjacent mica components, preventing frictional detachment and effectively improving overall wear resistance.
[0028] The nano-ceramic filler includes at least one of the following: nano-α-phase alumina, nano-tetragonal zirconium oxide, nano-magnesium oxide, nano-yttrium oxide, nano-silicon dioxide, nano-aluminum nitride, nano-silicon nitride, nano-zirconium nitride, nano-zirconium boride, titanium nitride whiskers, and silicon nitride whiskers. The particle size of the nano-ceramic filler is 20-800 nm.
[0029] Preferably, the nano-ceramic filler is composed of 40-60 parts of nano-α-phase alumina with an average particle size of 10-200 nm, 5-20 parts of nano-tetragonal phase zirconia with an average particle size of 50-200 nm, 1-3 parts of nano-magnesium oxide with an average particle size of 50-200 nm, 1-3 parts of nano-silica with an average particle size of 20-50 nm, 1-3 parts of nano-aluminum nitride with an average particle size of 50-500 nm, 1-3 parts of nano-silicon nitride with an average particle size of 20-800 nm, 0.2-0.5 parts of titanium nitride whiskers, and 0.2-0.5 parts of silicon nitride whiskers; wherein the length of the titanium nitride whiskers and silicon nitride whiskers is 5-20 μm and the aspect ratio is 20-40.
[0030] The flexible mica substrate is made from a combination of silicone resin and mica through a hot-pressing process. The thickness of the flexible mica substrate is controlled at 0.20-1.0 mm, and the adhesive content is controlled at 10-16 wt%. Preferably, the thickness of the flexible mica substrate is controlled at 0.20-0.40 mm, and the adhesive content is controlled at 12-14 wt%.
[0031] The mica composition is composed of mica powder treated with a surface modifier and toughening filler in a mass ratio of (90-98):(2-10).
[0032] The mica powder in the mica composition is at least one of phlogopite, muscovite, biotite, and fluorophlogopite. The toughening filler is at least one of aramid staple fiber, glass staple fiber, γ-alumina fiber, and aluminum borate whiskers. The particle size of the mica powder in the mica composition is 30-60 μm. The length of the aramid staple fiber, glass staple fiber, and γ-alumina fiber in the toughening filler is 10-500 μm. The particle size of the aluminum borate whiskers is 0.3-10 μm. The surface modifier in the mica composition is at least one of methacryloyloxysilane, vinyl silane, and titanate coupling agent.
[0033] Preferably, the mica powder in the mica composition is composed of phlogopite powder and fluorophlogopite in a mass ratio of (3-4):1. The mica composition is composed of mica powder treated with a surface modifier and toughening filler in a mass ratio of (94-96):(4-6). The toughening filler is composed of aramid staple fiber and aluminum borate whiskers in a mass ratio of (90-98):(2-10). The aramid staple fiber is Kevlar aramid staple fiber with a fineness of 2-3 DTEX and a length of 0.2-0.4 mm (customized by Changzhou Yaobang Friction Materials Factory). The surface modifier is composed of methacryloyloxysilane KH570, vinyl silane KH-151, and titanate coupling agent KR 138S in a mass ratio of (1-4):(1-4):(0.5-2).
[0034] The organosilicon resin is made from 100 parts of methylphenyl silicone resin, 25-60 parts of organic solvent, 0.3-0.6 parts of diethylenetriamine, 40-60 parts of polysiloxane crosslinking agent, and 1-3 parts of nano-sized vitrified ceramic powder. The polysiloxane crosslinking agent is at least one of JNC's FM-3321 type diamine-terminated reactive silicone, FM-3325 type diamine-terminated reactive silicone, FM-7721 type diacetyl reactive silicone, and FM-7725 type diacetyl reactive silicone. Preferably, the polysiloxane crosslinking agent is composed of JNC's FM-3325 type diamine-terminated reactive silicone and FM-7721 type diacetyl reactive silicone in a molar ratio of (3-4):1.
[0035] The preparation method of organosilicon resin is as follows: Accurately metered polysiloxane crosslinking agent, methylphenyl silicone resin, and diethylenetriamine (40-60% of the total mass of diethylenetriamine) are added to a reaction vessel. The mixture is heated to 60-65℃ at a magnetic stirring speed of 60-120 rpm and held for 100-160 seconds. After cooling to 0-4℃ via an ice-salt bath, an organic solvent is added, and the mixture is stirred at 80-160 rpm for 5-10 minutes. Then, the remaining diethylenetriamine is added, and the mixture is stirred at 40-60 rpm for 100-160 seconds to obtain the organosilicon resin. The storage temperature of the obtained organosilicon resin should be controlled at 0-4℃.
[0036] A method for preparing a high wear-resistant mica composite material for new energy vehicle batteries, the specific steps of which are as follows: Step 1: Prepare the silicone resin and simultaneously treat the mica composition with a surface treatment agent. Step 2: The prepared silicone resin and the mica composition treated with the surface treatment agent are mixed evenly to obtain a molded mica slurry. The molded mica slurry is transferred to a hot press mold. The mold temperature of the hot press mold is adjusted to 75-78℃ to remove the organic solvent components in the molded mica slurry. Then, a stainless steel mold plate is used for leveling and molding to obtain a preform. The molding surface of the stainless steel mold plate has a grid groove, and the surface of the preform has a grid-shaped groove area. Step 3: Mix the prepared nano-ceramic filler with high-purity nitrogen gas at a ratio of (0.1-2):(98-99.9) to form a deposition gas. The resulting deposition gas has a flow rate of 0.3-0.5 m / s. The sedimentation area formed between the delivery pipe of the deposition gas and the preform moves along the length of the preform at a speed of 4-8 cm / s, thus performing a full-coverage sedimentation treatment on the surface of the preform. Step four: First hot pressing treatment, platen temperature 80±0.5℃, pressure 0.20-0.25Mpa, continuous hot pressing time 60±2s; Second hot pressing treatment, platen temperature 130±0.5℃, pressure 0.50-0.60Mpa, continuous hot pressing time 120±2s; Third hot pressing treatment, platen temperature 180±0.5℃, pressure 0.80-1.0Mpa, continuous hot pressing time 150±5s; Fourth hot pressing treatment... The pressing plate temperature is 120±0.5℃, the pressure is 0.50-0.60Mpa, the continuous hot pressing time is 60±5s, and after cooling to 80-85℃, laser sintering is performed. The laser sintering parameters are: laser diameter 0.02-0.08mm, laser power 120-240W, scanning rate 0.2-0.4mm / s, and the laser scanning path moves along the length of the obtained preform to perform 1-2 full-coverage laser sintering treatments. After cooling to room temperature, a high wear-resistant flexible mica composite material is obtained.
[0037] Example 1: A high-wear-resistant mica composite material for new energy vehicle batteries includes a flexible mica substrate. The flexible mica substrate is made of an organosilicon resin and a mica composition through a hot-pressing process, with a thickness controlled at 0.40 mm ± 0.02 mm and a glue content controlled at 14 wt%. The mica powder in the mica composition is composed of phlogopite powder with an average particle size of 30-60 micrometers and fluorophlogopite in a mass ratio of 4:1. The mica composition is composed of mica powder treated with a surface modifier and toughening filler in a mass ratio of 95:5; the toughening filler is composed of aramid short fibers and aluminum borate whiskers in a mass ratio of 96:4. The aramid short fibers are Kevlar aramid short fibers with a fineness of 2.02 DTEX and a length of 0.30 mm. The surface modifier is composed of methacryloyloxysilane KH570, vinylsilane KH-151, and titanate coupling agent KR 138S in a mass ratio of 2:2:1. The silicone resin selected was Shin-Etsu KR-242A silicone resin (50% solid content) from Japan.
[0038] A grooved region is integrally formed on the surface of a flexible mica substrate by hot pressing, and the grooved region is filled with nano-ceramic filler. The nano-ceramic filler consists of 45 parts of nano-α-phase alumina (Chaowei Nano CW-Al2O3-002) with an average particle size of 50 nm, 15 parts of nano-tetragonal zirconium oxide (Chaowei Nano CW-ZrO2-002) with an average particle size of 500 nm, 1 part of nano-magnesium oxide (Chaowei Nano CW-MgO-001) with an average particle size of 50 nm, 1 part of nano-silica (Chaowei Nano CW-SiO2-001) with an average particle size of 20 nm, 2 parts of nano-aluminum nitride (Chaowei Nano CW-AlN-001) with an average particle size of 50 nm, 3 parts of nano-silicon nitride (Chaowei Nano CW-Si3N4-001) with an average particle size of 20 nm, 0.2 parts of titanium nitride whiskers, and 0.3 parts of silicon nitride whiskers. The titanium nitride whiskers (model AM-TiN-W-01, Yamei Nano) and silicon nitride whiskers (model AM-Si3N4-W-2, Yamei Nano) have a length of 10-20 μm and an aspect ratio of 20-40. The nano-ceramic fillers located in the grooved areas on the surface of the flexible mica substrate are laser-sintered to form "ceramic solidification bridges." These bridges connect adjacent mica compositions, preventing frictional detachment.
[0039] The preparation method of a high wear-resistant mica composite material for new energy vehicle batteries has the following steps: Step 1: Surface-treat the mica composition using a surface treatment agent: Preparation of surface treatment solution: 4g of methacryloxysilane KH570, 4g of vinylsilane KH-151, and 2g of titanate coupling agent KR 138S are dissolved in 1000mL of deionized water to form the surface treatment solution. Meanwhile, phlogopite powder and fluorophlogopite with an average particle size of 30-60 micrometers are mixed in a mass ratio of 4:1 to obtain mica powder. 50g of mica powder is weighed and placed in 500mL of surface treatment liquid for ultrasonic dispersion treatment for 1.0h. After leaching and low-temperature drying, surface-modified mica powder is obtained. Aramid staple fiber and aluminum borate whiskers are mixed at a mass ratio of 96:4 to obtain a toughening filler. 2.5g of the toughening filler is weighed and placed in 100mL of surface treatment liquid for 1.0h ultrasonic dispersion treatment. After leaching and low-temperature drying, the toughening filler treated with surface modifier is obtained. Mica powder treated with surface modifier and toughening filler are mixed at a mass ratio of 95:5 to obtain the finished mica composition. Step 2: Mix 280g of KR-242A silicone resin (50% solid content) from Shin-Etsu Chemical Co., Ltd. of Japan with 860g of the mica composition treated with the surface treatment agent prepared in Step 1 to obtain a molded mica slurry. Transfer the molded mica slurry into a hot press mold. Adjust the mold temperature of the hot press mold to 120°C to remove the organic solvent components (toluene and isopropanol) in the molded mica slurry. Then, use a stainless steel mold plate to perform leveling and molding treatment to obtain a preform. The molding surface of the stainless steel mold plate is formed with a grid groove with a groove depth of 5.0 micrometers and an interval of 100 micrometers between adjacent grooves. The molding temperature is 78°C and the pressure is 0.6MPa, which can form a grid-shaped groove area on the surface of the preform. Step 3: Mix the prepared nano-ceramic filler with high-purity nitrogen at a ratio of 0.6:98-99.4 to form a deposition gas. The resulting deposition gas has a flow rate of 0.3 m / s. The deposition gas delivery pipe and the sedimentation area formed between the preform move along the length of the preform at a speed of 4 cm / s, thus performing a full-coverage sedimentation treatment on the surface of the preform. Step four: First hot pressing treatment, platen temperature 80±0.5℃, pressure 0.20Mpa, continuous hot pressing time 60s; Second hot pressing treatment, platen temperature 130±0.5℃, pressure 0.60Mpa, continuous hot pressing time 120s; Third hot pressing treatment, platen temperature 180±0.5℃, pressure 0.80Mpa, continuous hot pressing time 150s; Fourth hot pressing treatment, platen temperature 120±0.5℃, pressure 0.50Mpa, continuous hot pressing time 60s. After cooling to 80℃, laser sintering treatment is performed. Laser sintering treatment parameters: laser diameter 0.04mm, laser power 150W, scanning rate 0.2mm / s, laser scanning path moves along the length of the obtained preform for one full-coverage laser sintering treatment. After cooling to room temperature, a high wear-resistant flexible mica composite material is obtained.
[0040] The difference between Example 2 and Example 1 is that the silicone resin is made from 100 parts of methylphenyl silicone resin, 30 parts of organic solvent (methanol), 0.38 parts of diethylenetriamine, 40 parts of polysiloxane crosslinking agent, and 1.12 parts of nano-sized vitreous ceramic powder. The polysiloxane crosslinking agent is JNC's FM-3325 type diamine reactive silicone and FM-7721 type diacetyl reactive silicone in a molar ratio of 3:1.
[0041] The preparation method of organosilicon resin is as follows: 45g of accurately measured FM-3325 type diamine reactive silicone, 15g of FM-7721 type diacetyl reactive silicone, 100g of methylphenyl silicone resin (solid content of 50%), and 0.2g of diethylenetriamine are added to a reaction vessel. The mixture is heated to 65℃ at 80rpm with magnetic stirring and held for 120s. After cooling to 0-4℃ through an ice-salt bath, an organic solvent is added and stirred at 80rpm for 5min. Then, the remaining diethylenetriamine is added and stirred at 60rpm for 120s to obtain the matrix organosilicon resin. The storage temperature of the obtained matrix organosilicon resin should be controlled at 0-4℃.
[0042] Step 2: Mix 280g of Shin-Etsu KR-242A silicone resin (50% solid content) from Japan with 860g of the mica composition treated with the surface treatment agent prepared in Step 1 to obtain a molded mica slurry. Transfer the molded mica slurry into a hot press mold. Adjust the mold temperature of the hot press mold to 75°C to remove the organic solvent components (toluene and isopropanol) from the molded mica slurry. Then, use a stainless steel mold plate to perform leveling and molding treatment to obtain a preform. The molding surface of the stainless steel mold plate has a grid-shaped groove with a groove depth of 5.0 micrometers and an interval of 100 micrometers between adjacent grooves. The molding temperature is 78°C and the pressure is 0.6MPa, which forms a grid-shaped groove area on the surface of the preform.
[0043] The difference between Example 3 and Example 1 is as follows: Laser sintering parameters: laser diameter 0.04mm, laser power 150W, scanning rate 0.3mm / s, the laser scanning path moves along the length of the obtained preform to perform one full-coverage laser sintering treatment, and the high wear-resistant flexible mica composite material is obtained by cooling to room temperature.
[0044] The difference between Example 4 and Example 1 is as follows: Laser sintering parameters: laser diameter 0.04mm, laser power 150W, scanning rate 0.4mm / s, the laser scanning path moves along the length of the obtained preform to perform one full-coverage laser sintering treatment, and the high wear-resistant flexible mica composite material is obtained by cooling to room temperature.
[0045] The difference between Example 5 and Example 1 is as follows: Laser sintering parameters: laser diameter 0.04mm, laser power 150W, scanning rate 0.4mm / s, the laser scanning path moves along the length of the obtained preform to perform two full-coverage laser sintering processes, and the high wear-resistant flexible mica composite material is obtained by cooling to room temperature.
[0046] The difference between Example 6 and Example 1 is as follows: In step three, the prepared nano-ceramic filler is mixed with high-purity nitrogen at a ratio of 0.6:98-99.4 to form a deposition gas. The resulting deposition gas has a flow rate of 0.4 m / s. The sedimentation area formed between the delivery pipe of the deposition gas and the preform moves along the length of the preform at a speed of 6 cm / s, thus performing a full-coverage sedimentation treatment on the surface of the preform.
[0047] The difference between Example 7 and Example 1 is as follows: In step three, the prepared nano-ceramic filler is mixed with high-purity nitrogen at a ratio of 0.6:98-99.4 to form a deposition gas. The resulting deposition gas has a flow rate of 0.5 m / s. The sedimentation area formed between the delivery pipe of the deposition gas and the preform moves along the length of the preform at a speed of 8 cm / s, thus performing a full-coverage sedimentation treatment on the surface of the preform.
[0048] The difference between Example 8 and Example 2 is that the nano-ceramic filler is composed of 45 parts of nano-α-phase alumina with an average particle size of 200 nm, 15 parts of nano-tetragonal phase zirconia with an average particle size of 50 nm, 1 part of nano-magnesium oxide with an average particle size of 50 nm, 1 part of nano-silica with an average particle size of 20 nm, 2 parts of nano-aluminum nitride with an average particle size of 500 nm, 3 parts of nano-silicon nitride with an average particle size of 800 nm, 0.2 parts of titanium nitride whiskers, and 0.3 parts of silicon nitride whiskers.
[0049] The difference between Comparative Example 1 and Example 1 is as follows: In step four, the first hot pressing process is carried out at a platen temperature of 80±0.5℃, a pressure of 0.20 MPa, and a continuous hot pressing time of 60s; the second hot pressing process is carried out at a platen temperature of 130±0.5℃, a pressure of 0.60 MPa, and a continuous hot pressing time of 120s; the third hot pressing process is carried out at a platen temperature of 180±0.5℃, a pressure of 0.80 MPa, and a continuous hot pressing time of 150s; the fourth hot pressing process is carried out at a platen temperature of 120±0.5℃, a pressure of 0.50 MPa, and a continuous hot pressing time of 60s. After cooling to room temperature, a high wear-resistant flexible mica composite material is obtained.
[0050] The difference between Comparative Example 2 and Example 1 is as follows: Laser sintering processing parameters: laser diameter 0.04mm, laser power 150W, scanning rate 0.1mm / s, the laser scanning path moves along the length direction of the obtained preform to perform one full-coverage laser sintering process, and the high wear-resistant flexible mica composite material is obtained by cooling to room temperature.
[0051] The difference between Comparative Example 3 and Example 1 is as follows: Laser sintering parameters: laser diameter 0.04 mm, laser power 150 W, scanning rate 0.6 mm / s, the laser scanning path moves along the length direction of the obtained preform to perform two full-coverage laser sintering treatments, and the high wear-resistant flexible mica composite material is obtained by cooling to room temperature.
[0052] The difference between Comparative Example 4 and Example 1 is as follows: In step three, the prepared nano-ceramic filler is mixed with high-purity nitrogen at a ratio of 0.6:98-99.4 to form a deposition gas. The resulting deposition gas has a flow rate of 0.25 m / s. The sedimentation area formed between the delivery pipe of the deposition gas and the preform moves along the length of the preform at a speed of 10 cm / s, thus performing a full-coverage sedimentation treatment on the surface of the preform.
[0053] The difference between Comparative Example 5 and Example 1 is as follows: In step three, the prepared nano-ceramic filler is mixed with high-purity nitrogen at a ratio of 0.6:98-99.4 to form a deposition gas. The resulting deposition gas has a flow rate of 0.55 m / s. The sedimentation area formed between the delivery pipe of the deposition gas and the preform moves along the length of the preform at a speed of 4 cm / s, thus performing a full-coverage sedimentation treatment on the surface of the preform.
[0054] The difference between Comparative Example 6 and Example 1 is that the nano-ceramic filler is composed of 45 parts of nano-α-phase alumina with an average particle size of 50 nm, 15 parts of nano-tetragonal phase zirconia with an average particle size of 500 nm, 1 part of nano-magnesium oxide with an average particle size of 50 nm, 1 part of nano-silica with an average particle size of 20 nm, and 5.5 parts of potassium feldspar (first-grade).
[0055] The performance testing methods are as follows: Thermal conductivity test method: determined according to GB / T 10295-2008. Flame retardancy test method: determined according to UL94 V-0 flame retardancy test standard. Breakdown voltage test method: determined according to ASTM D149-09. Adhesive content test: tested according to GB / T 5019.2-2009, Clause 8.4.5, "Unreinforced materials with silicone adhesives (insoluble adhesives)". Density test: determined according to GB / T 5019.2-2009, Mica Products Test Methods, Clause 6, "Density". Abrasion resistance test methods are as follows: Abrasion strength test method: tested according to GB / T3960-2016, Plastics Sliding Friction and Wear Test Method.
[0056] Flexibility test method: The test sample size is 40cm in length and 20cm in width. The flexible mica substrates in Examples 1-6 and Comparative Examples 1-8 are placed on a steel roller with a diameter of 12cm for bending test. The flexible mica substrate is wound around the steel roller and bent. When the flexible mica substrate breaks near the bending point, the acute angle formed by the flexible mica substrate above the center horizontal plane of the steel roller and the center horizontal plane of the steel roller is recorded as A1. The acute angle formed by the flexible mica substrate below the center horizontal plane of the steel roller and the center horizontal plane of the steel roller is recorded as A2. The angle obtained is A1 + A2, which is the maximum bending angle of the flexible mica substrate.
[0057] As can be seen from Examples 1-6 and Comparative Examples 1-8, and from Examples 1-2 and Comparative Example 1, and from Examples 2 and 8, the flexible mica substrate prepared using the self-made silicone resin has superior flexibility.
[0058] As can be seen from Examples 1-6 and Comparative Examples 1-8, Examples 1, 3-5 and Comparative Examples 2-3 show that the laser sintering parameters during the preparation process are: laser diameter 0.02-0.08mm, laser power 120-240W, scanning rate 0.2-0.4mm / s, and the laser scanning path should move along the length of the obtained preform to perform 1-2 full-coverage laser sintering treatments. This can ensure that the prepared flexible mica substrate has better flexibility and wear resistance.
[0059] As can be seen from Examples 1-6 and Comparative Examples 1-8, Examples 1, 6-7 and Comparative Examples 4-5 show that during the preparation process, the nano-ceramic filler and high-purity nitrogen are mixed at a ratio of (0.1-2):(98-99.9) to form a deposition gas. The flow rate of the resulting deposition gas is 0.3-0.5 m / s. The sedimentation area formed between the delivery pipe of the deposition gas and the preform moves along the length of the preform at a speed of 4-8 cm / s. It is advisable to perform a full-coverage sedimentation treatment on the surface of the preform to ensure that the prepared flexible mica substrate has better flexibility and wear resistance.
[0060] In summary, this application possesses excellent fire-retardant safety performance, insulation and breakdown resistance, as well as good wear resistance and a certain degree of flexibility. When used in automotive battery cells, it can improve the thermal runaway protection safety performance of the entire vehicle.
[0061] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A high-wear-resistant mica composite material for new energy vehicle batteries, characterized in that: The product includes a flexible mica substrate, which is manufactured by hot pressing a composition of silicone resin and mica. Grooves are integrally formed on the surface of the flexible mica substrate by hot pressing. These grooves are filled with ceramic filler. The ceramic filler consists of 40-60 parts of nano-α-phase alumina with an average particle size of 10-200 nm, 5-20 parts of nano-tetragonal phase zirconia with an average particle size of 50-200 nm, 1-3 parts of nano-magnesium oxide with an average particle size of 50-200 nm, and 1-3 parts of nano-dioxide with an average particle size of 20-50 nm. The composition comprises silicon, 1-3 parts of nano-aluminum nitride with an average particle size of 50-500nm, 1-3 parts of nano-silicon nitride with an average particle size of 20-800nm, 0.2-0.5 parts of titanium nitride whiskers, and 0.2-0.5 parts of silicon nitride whiskers; the lengths of the titanium nitride whiskers and silicon nitride whiskers are 5-20μm, and the aspect ratios are 20-40; the ceramic filler located in the groove area formed on the surface of the flexible mica substrate is laser-sintered to form "ceramic solidification bonds", which connect adjacent mica compositions together and are not prone to frictional detachment.
2. The high wear-resistant mica composite material for new energy vehicle batteries according to claim 1, characterized in that: The thickness of the flexible mica substrate is controlled at 0.20-1.0 mm, and the adhesive content is controlled at 10-16 wt%. The mica composition is composed of mica powder treated with a surface modifier and toughening filler in a mass ratio of (90-98):(2-10). The mica powder in the mica composition is at least one of phlogopite powder, muscovite, biotite, and fluorophlogopite. The toughening filler is at least one of aramid short fiber, glass short fiber, γ-alumina fiber, and aluminum borate whiskers.
3. The high wear-resistant mica composite material for new energy vehicle batteries according to claim 2, characterized in that: The mica powder in the mica composition has a particle size of 30-60 μm; the aramid short fibers, glass short fibers, and γ-alumina fibers in the toughening filler have a length of 10-500 μm; the aluminum borate whiskers have a particle size of 0.3-10 μm; and the surface modifier in the mica composition is at least one of methacryloyloxysilane, vinyl silane, and titanate coupling agent.
4. The high wear-resistant mica composite material for new energy vehicle batteries according to claim 3, characterized in that: The thickness of the flexible mica substrate is controlled at 0.20-0.40 mm, and the adhesive content is controlled at 12-14 wt%. The mica powder in the mica composition is composed of phlogopite powder and fluorophlogopite in a mass ratio of (3-4):
1. The mica composition is composed of mica powder treated with a surface modifier and toughening filler in a mass ratio of (94-96):(4-6). The toughening filler is composed of aramid staple fiber and aluminum borate whiskers in a mass ratio of (90-98):(2-10). The aramid staple fiber is Kevlar aramid staple fiber with a fineness of 2-3 DTEX and a length of 0.2-0.4 mm. The surface modifier is composed of methacryloyloxysilane KH570, vinyl silane KH-151, and titanate coupling agent KR 138S in a mass ratio of (1-4):(1-4):(0.5-2).
5. A method for preparing a high-wear-resistant mica composite material for new energy vehicle batteries according to any one of claims 1-4, characterized in that: Includes the following steps: Step 1: Prepare the silicone resin and simultaneously treat the mica composition with a surface treatment agent. Step 2: The prepared silicone resin and the mica composition treated with the surface treatment agent are mixed evenly to obtain a molded mica slurry. The molded mica slurry is transferred to a hot press mold and heated to remove the organic solvent components in the molded mica slurry. Then, a stainless steel mold plate is used to perform leveling and molding treatment to obtain a preform. The molding surface of the stainless steel mold plate is formed with a grid groove, and the surface of the preform is formed with a grid-shaped groove area. Step 3: Mix the prepared ceramic filler with high-purity nitrogen gas at a ratio of (0.1-2):(98-99.9) to form a deposition gas. The resulting deposition gas has a flow rate of 0.3-0.5 m / s. The sedimentation area formed between the delivery pipe of the deposition gas and the preform moves along the length of the preform at a speed of 4-8 cm / s, thus performing a full-coverage sedimentation treatment on the surface of the preform. Step four: First hot pressing treatment, with a platen temperature of 80±0.5℃, a pressure of 0.20-0.25Mpa, and a continuous hot pressing time of 60±2s; Second hot pressing treatment, with a platen temperature of 130±0.5℃, a pressure of 0.50-0.60Mpa, and a continuous hot pressing time of 120±2s; Third hot pressing treatment, with a platen temperature of 180±0.5℃, a pressure of 0.80-1.0Mpa, and a continuous hot pressing time of 150±5s; Fourth hot pressing treatment, with a platen temperature of 120±0.5℃, a pressure of 0.50-0.60Mpa, and a continuous hot pressing time of 60±5s. After cooling to 80-85℃, laser sintering is performed to obtain a high wear-resistant flexible mica composite material.
6. The method for preparing a high wear-resistant mica composite material for new energy vehicle batteries according to claim 5, characterized in that: The laser sintering parameters are as follows: laser diameter 0.02-0.08mm, laser power 120-240W, scanning rate 0.2-0.4mm / s, and the laser scanning path moves along the length of the obtained preform to perform 1-2 full-coverage laser sintering processes. After cooling to room temperature, a high wear-resistant flexible mica composite material is obtained.
Citation Information
Patent Citations
Graphical flexible transparent conductive film and preparation method thereof
CN102222538A
Ceramic grid-enhanced metal wear-resistant composite and preparation method thereof
CN102225469A